Mechanical properties of the premature lung: From tissue deformation under load to mechanosensitivity of alveolar cells - Naumann, Jonas; Koppe, Nicklas; Thome, Ulrich H.; Laube, Mandy; Zink, Mareike (Frontiers in Bioengineering and Biotechnology, 2022)
Many preterm infants require mechanical ventilation as life-saving therapy. However, ventilation-induced overpressure can result in lung diseases. To elucidate the effect of positive pressure on lung tissue mechanics and cell behavior, we mimic the effect of overpressure by employing a uniaxial load onto fetal and adult rat lungs with different deformation rates. In contrast, tissue expansion during tidal breathing was addressed by uniaxial tension. We found a hyperelastic deformation behavior of fetal tissues under compression and tension with a remarkable strain stiffening. In contrast, adult lungs exhibited a similar response only during compression. Young’s moduli were always larger during tension compared to compression, while only during compression a strong deformation-rate dependency was found. In fact, fetal lung tissue under compression showed clear viscoelastic features even for small strains. Thus, we propose that the fetal lung is much more vulnerable during inflation by mechanical ventilation compared to normal inspiration. Electrophysiological experiments with different hydrostatic pressure gradients acting on primary fetal distal lung epithelial cells revealed that the activity of the epithelial sodium channel (ENaC) and the sodium-potassium pump (Na,K-ATPase) dropped during pressures of 30 cmH2O. Thus, pressures used during mechanical ventilation might impair alveolar fluid clearance important for normal lung function.